A new strategy for taste masking on bitter drug by other combined drug in fixed-dose combination: bitterness of Amlodipine besylate could be masked efficiently by Valsartan. (5th July 2019) - Kojima, Honami; Nakamura, Saki; Haraguchi, Tamami; Yoshida, Miyako; Habara, Masaaki; Ikezaki, Hidekazu; Uchida, Takahiro
Abstract: Objectives: The aim of this study was to evaluate the bitterness of amlodipine besylate (AML) combined with other five antihypertensive drugs: alacepril, benazepril, hydrochlorothiazide, telmisartan (TEL) and valsartan (VAL), which have possibility of usage as a fixed-dose combination (FDC) drugs. Methods: The bitterness of individual six drugs and AML combined with each of the five drugs was evaluated using taste sensor SA402B (Intelligent Sensor Technology Inc.). AML combined with TEL or VAL was evaluated by taste sensor and human gustatory sensation tests. The interaction between AML with TEL or VAL was evaluated by 1 H-NMR. Key findings: The bitterness of AML was significantly decreased by addition of VAL, whereas it remained unchanged by the addition of TEL in taste sensor and human gustatory sensation test. In the 1 H-NMR spectrum of AML with VAL, signal shifts of protons in AML were observed compared to that in AML alone. On the other hand, in the 1 H-NMR spectrum of AML with TEL, signal shifts of protons in AML were not observed. Conclusions: It was suggested that when VAL was mixed with AML, the electrostatic interactions between positive charged amino group of AML and negative charged tetrazole group of VAL were caused, and thereby led the suppression the bitterness of AML.